Identification of Prosocial Behavior in the LDP Tagana COVID-19 Team at the Sayyid Ali Rahmatullah Tulungagung State Islamic University - Agustina, Mirna Wahyu; Mubarok, Ali Syahidin (Universitas Negeri Malang, 2023)
The COVID-19 outbreak has had a tremendous impact, including the number of health workers who died due to exposure to COVID-19. This causes the need for personnel to deal with COVID-19, both medically and non-medically, to increase. These conditions make some people want to contribute and decide to become volunteers. Becoming a volunteer cannot be separated from prosocial behavior, where several factors also influence prosocial behavior. This research aims to look at several factors that influence prosocial behavior. This research used six independent variables: social support, empathy, altruism, cooperation, dyadic coping, and volunteerism, and one dependent variable, prosocial behavior. The approach used is quantitative with multiple linear regression analysis. The population of this study was all 32 members of the LDP Tagana COVID-19 Team at the Sayyid Ali Rahmatullah Tulungagung State Islamic University Flats. All members of the population were involved in this research. The sampling technique used was total sampling. The data collection instrument uses a Likert scale with four answer choices. As for the results, there is a significant influence both simultaneously and partially. Simultaneously, the influence given was 63.9%, while the rest was explained by other variables not examined in this research. This research shows that prosocial behavior can be formed by the factors used in this research. It is very possible that prosocial behavior can be shaped by other variables not examined in this research.